Preparation and electrical conductivity of (Cu0.5Ag0.5)7SiS5I-based superionic ceramics - Studenyak Ihor; Студеняк Ігор; Pogodin Artem; Погодін Артем; Shender Iryna; Шендер Ірина; Bereznyuk Serhiy; Сергій Березнюк; Filep Mykhailo; Філеп Михайло; Filep Mihály; Oleksandr Kokhan; et al. (My University, 2021)
Abstract. The ceramics based on (Cu05Ag0.5)7SiS5I solid solution of superionic conductor with argyrodite structure were prepared by using the powders with different particles size. The structural studies of powders were performed by XRD technique, while the ceramic samples with different average size of the crystallites were investigated by microstructural analysis. The total electrical conductivity of ceramic samples was measured by impedance spectroscopy in the frequency range from 10 Hz to 2 106 Hz and temperature interval from 292 K to 383 K. The contributions of ionic and electronic components into the total electrical conductivity were separated as well as their temperature behavior was studied. The dependences of ionic and electronic conductivity and their activation energies on average size of the crystallites in (Cu0$5Ag0.5)7SiS5I-based ceramic samples were investigated.
Editorial board: https://www.sciencedirect.com/journal/journal-of-alloys-and-compounds/about/editorial-board Contents: https://www.sciencedirect.com/journal/journal-of-alloys-and-compounds/vol/854/suppl/C
Keywords: Argyrodite; Superionic conductor; Ceramic; Ionic conductivity; Activation energy